Income Effects from Labor Market Training Programs in Sweden During the 80's and 90's - Thomas Andrén; Björn Gustafsson (Institute for the Study of Labor (IZA), 2002)
Swedish labor market programs appear large from an international perspective, yet their consequences are not fully investigated and understood. In this paper we estimate a switching regression model with training effect modeled as a random coefficient, partitioned in an observed and unobserved component. We investigate labor market training for three cohorts during the 80s and the beginning of the 90s on its effect on earnings. We separate the analysis between Swedish-born and foreign-born individuals to identify differences in their responses to training. The results indicate that there is positive sorting into training. We find that the proportion of trainees having positive rewards from training was not very different from the proportion having negative rewards. This means that the results do not support the view that from efficiency considerations, too few persons were enrolled in labor market training during this period. Differences in results across cohorts can be interpreted as being caused by rapid changes in the labor market. Further, consistent with results from several previous studies we find that being young often means no positive pay-off from training, and the same is found for persons with only primary education. In conflict with what earlier studies have shown, we found that males have a better pay-off from training than females. Rewards from training were higher for foreign-born than for natives and rewards among the former vary by place of birth.
Keywords: J38; J31; 330; labor market training; non-experimental estimator; positive sorting; unobserved heterogeneity to training reward; random coefficient model; Berufsbildungspolitik; Arbeitsmarktpolitik; Bildungsertrag; Zustandsraummodell; Schätzung; Theorie